Private Activity in Energy Down, But Still Around Peak Levels - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Private activity in energy showed mixed results in 2008, according to just-released data from the Private Participation in Infrastructure Project database. Although investment commitments to energy projects with private participation were down, they remained strong at the third highest level in 1990-2008. Activity in the first half of 2008 kept investment at a high level for the year. Investment slowed in the second half with the full onset of the financial crisis. The slowdown in the second half also led to a decline in the number of projects for the year. In 2008, 86 energy projects with private participation reached financial or contractual closure in 23 low- and middle-income countries. These involve investment commitments (hereafter, investment) of US$37.2 billion. Energy projects implemented in previous years had additional commitments of US$10.39 billion, bringing total investment in 2008 to US$47.5 billion. That represents a drop of 7 percent from the level reported in 2007. Lower payments to governments (such as concession or lease fees and divestiture revenues) account for the decline. By contrast, investment in physical assets, which amounted to US$38.7 billion in 2008, was up 6 percent from that reported in 2007.